Application of The Double Exponential Smoothing Brown Method to Consumer Price Index Forecasting in Sorong City before and during The Covid-19 Pandemic - Nurin Hidayah; Esther Ria Matulessy; Rium Hilum (Journal of Social Research, 2024)
The CPI is useful for knowing the increase in income, prices, can also be used as an economic indicator and a benchmark for the amount of production costs. The Consumer Price Index is often used to measure the level of increase or decrease (inflation/deflation) in the prices of goods and services that are the basic needs of the people of an area, as well as a consideration for salary adjustments, retirement wages and others. CPI forecasting in Sorong City is a solution to predict future economic conditions as seen from the increase or decrease in the CPI and choose the right countermeasure or strategy in dealing with the consequences of an increase (inflation) or decrease (deflation) in the CPI that will occur in the future. The Covid-19 Pandemic situation has greatly affected economic and social life, including the CPI in Sorong City. The purpose of this research is to obtain the right model in forecasting the CPI in Sorong City using the Double Exponential Smoothing Brown method, a forecasting method that uses one weighting parameter. The best model of forecasting before the Covid-19 pandemic using optimal weighting parameters with a MAPE value of 0.647%, namely: and the best model during the Covid-19 pandemic using optimal weighting parameters with a MAPE value of 0.633%. The forecasting model obtained, namely: